PELATIHAN AKUNTANSI DAN PENYUSUNAN LAPORAN KEUANGAN BAGI MANAJER DAN STAF KEUANGAN KOPERASI USAHA PENANAMAN DAN PENGOLAHAN KOPI DI KABUPETEN ACEH TENGAH DAN BENER MERIAH - BZ, Fazli Syam; Iskandarsyah, Iskandarsyah; Evayani, Evayani; Afrianandra, Cut (UNIVERSITAS PGRI MADIUN, 2018)
Abstract. The accounting and financial reporting training aims to provide knowledge (methods / techniques) and accounting practices that start from the accounting cycle in preparing financial statements for cooperative managers and finance staff towards transparent, accountable, accountable, self-sustaining and transparent cooperative governance justice. The cooperative must have a reliable and valid financial management system so that cooperative management that is familial and mutual cooperation requires the active participation and participation of all stakeholders.The training was conducted at the Coffe and Coffeemaking Cooperative in Central Aceh and Bener Meriah Regency involving 45 participants from 13 cooperatives consisting of Managers and Finance Staff. The training was conducted for 3 (three) dated March 17 - 19, 2017. In the initial phase, training needs analysis has been done to obtain preliminary information about understanding and accounting practices in the targeted cooperatives.The final outcomes of training for cooperatives are the preparation of the Preliminary Balance Sheet and the Financial Statements of Cooperatives for the period of December 31, 2016 and the continuing recording of transactions for the period of 2017 until the preparation of the Financial Statements of December 31, 2017.Keywords: Accounting, Financial Statement, Cooperative, Governance Abstrak.Pelatihan akuntansi dan penyusunan laporan keuangan ini bertujuan untuk memberikan pengetahuan (metode/teknik) dan praktik akuntansi yang dimulai dari siklus akuntansi dalam menyusun laporan keuangan bagi para manajer dan staf keuangan koperasi guna menuju tata kelola koperasi yang transparan, akuntabel, bertanggungjawab, mandiri, dan berkeadilan. Koperasi harus memiliki sistem manajemen keuangan yang handal dan valid sehingga tata kelola koperasi yang bersifat kekeluargaan dan gotong royong menuntut peran dan partisipasi aktif dari seluruh anggota (stakeholder). Pelatihan ini dilakukan pada Koperasi Usaha Penamanan dan Pengolahan Kopi di Kabupaten Aceh Tengah dan Bener Meriah yang melibatkan 45 orang peserta dari 13 Koperasi yang terdiri dari Manajer dan Staf Keuangan. Pelatihan dilakukan selama 3 (tiga) tanggal 17 – 19 Maret 2017. Pada tahap awal telah dilakukan analisis kebutuhan pelatihan guna mendapatkan informasi awal tentang pemahaman dan praktik akuntansi pada koperasi yang disasar.Dampak akhir (outcome) dari pelatihan bagi koperasi adalah tersusunnya Neraca Awal dan Laporan Keuangan Koperasi untuk periode 31 Desember 2016 dan berlanjutnya pencatatan transaksi periode tahun 2017 sampai tersusunan Laporan Keuangan 31 Desember 2017.Kata Kunci: Akuntansi, Laporan Keuangan, Koperasi, Tata Kelola